Identifying the function of novel cross-species microRNAs from the excretory-secretory products of Angiostrongylus cantonensis fifth-stage larvae - Kuang-Yao Chen; Yi-Hsuan Lin; Chien-Ju Cheng; Yi-Hao Huang; Sheng-Yu Lin; Chyi-Liang Chen; Cheng-Hsun Chiu (Journal of Microbiology, Immunology and Infection)
Background: Angiostrongylus cantonensis is a significant foodborne zoonotic parasite that causes severe neuropathological damage and symptoms in humans. Excretory-secretory products (ESPs) play a pivotal role in elucidating host-parasite interactions and can aid in penetrating host defensive barriers in helminths. Recently, secreted microRNAs have become important research targets for parasite-host communication. In this study, we determined the expression and function of novel microRNAs from A. cantonensis L5 ESPs and evaluated the effect of target microRNAs on the molecular mechanisms of mouse astrocytes. Methods: Here, we employed next-generation sequencing (NGS) to establish the secreted microRNAs dataset. Next, we evaluated the effects of AcESPs-microRNAs in A. cantonensis ESPs treated astrocytes. Results: First, we established the secreted microRNA dataset, and then comprehensively verified the characteristics. Novel microRNAs were initially detected, and their expression was found. Moreover, the prediction results showed that these secreted microRNAs may regulate Wnt and mTOR signaling. Next, the data showed that the AcNOVEL55 microRNA reduced cell apoptosis generation via regulating the RhoA-Rock signaling pathway in A. cantonensis L5 ESPs treated mouse astrocytes. Moreover, we also demonstrated that the AcNOVEL31 microRNA can affect the inflammation activation via regulating the presenilin-1/GSK3B/β-catenin/NF-κB pathway. Finally, the concentrations of secreted IL-6 and IL-12 proteins were downregulated by AcNOVEL31 microRNA by influencing presenilin-1 expression. Conclusion: This is the first study to verify the molecular functions of novel microRNAs secreted by A. cantonensis. The discovery of the microRNA mechanisms by which cross-species parasitic nematodes influence hosts has advanced research on host-parasitic nematode interactions.